AB0294 Long-term comprehensive disease control with certolizumab pegol regardless of concomitant dmards: results from the japanese cohort. (23rd January 2014) - Tanaka, Y.; Yamamoto, K.; Takeuchi, T.; Yamanaka, H.; Ishiguro, N.; Eguchi, K.; Watanabe, A.; Origasa, H.; Okamoto, T.; Shoji, T.; Miyasaka, N.; Koike, T.
Abstract : Background: Two double-blind (DB) trials of the PEGylated Fc-free anti-TNF certolizumab pegol (CZP), J-RAPID 1 (with MTX) and HIKARI 2 (without MTX), have shown rapid reduction of rheumatoid arthritis (RA) signs and symptoms and inhibition of progression of structural damage in Japanese patients (pts) with active RA. Objectives: To evaluate long-term comprehensive (clinical, radiographic and functional) disease control of CZP and safety in active RA pts through 80 weeks (wks) of DB and open-label extension (OLE) in J-RAPID and HIKARI studies. Methods: The efficacy population was DB completers (DBC) originally assigned to CZP 200mg every 2 weeks (Q2W) group (approved dose) with ACR20 response at Wk12 or 14 (CZP-DBC: J-RAPID, n=63; HIKARI, n=81). During OLE, pts were treated with CZP 200mg Q2W or CZP 400mg Q4W. Of HIKARI CZP-DBC, 34 and 47 pts were treated with CZP monotherapy and CZP with concomitant non-MTX DMARDs, respectively. ACR20/50/70 response rates, DAS28(ESR) scores and disease activity states and HAQ-DI scores were analyzed using LOCF, and ΔmTSS using linear extrapolation. The safety population was all pts in DB and OLE study. Results: 87.3% (55/63) of J-RAPID CZP-DBC and 86.4% (70/81) of HIKARI CZP-DBC continued treatment with CZP to Wk80, with Wk80 ACR20/50/70 responses 96.8%/88.9%/49.2% and 81.5%/63.0%/48.1%, respectively (Figure ). Wk80 mean ΔmTSS from Wk0 was 0.15 and 1.39, mean ΔHAQ was -0.64 and -0.62, and DAS28(ESR) remission rate was 34.9% and 37.0% respectively. In HIKARI CZP-DBC, CZP efficacy was similar in monotherapy or with concomitant non-MTX DMARDs: Wk80 ACR20/50/70 responses 85.3%/64.7%/52.9% and 78.7%/61.7%/44.7%, mean ΔmTSS from Wk0 1.42 and 1.36, mean ΔHAQ -0.61 and -0.62, and DAS28(ESR) remission rate 32.4% and 40.4%, respectively. In HIKARI and J-RAPID DB, 75.8% (269/355) and 62.8% (120/191) pts treated with CZP and PBO respectively reported adverse events (AE). Most common AEs were infections. AE incident rates in OLE were similar to DB. No new safety signals were detected. Image/graph: Conclusions: CZP provided long-term clinical, functional and radiographic benefits regardless of concomitant MTX or other DMARDs in Japanese pts up to Wk80. Efficacy of CZP monotherapy was comparable to CZP with concomitant DMARDs. Continuous CZP treatment for 80 wks was well-tolerated with no new safety signals detected. References: Yamamoto K. Arthritis Rheum 2011;63(Suppl10);S474 Yamamoto K. Arthritis Rheum 2011;63(Suppl10);S476 Acknowledgements: The authors acknowledge Costello Medical Consulting for writing and editorial assistance which was funded by UCB Pharma. Disclosure of Interest: Y. Tanaka Grant/research support from: BMS, MSD, Chugai, Mitsubishi-Tanabe, Astellas, Abbott, Eisai, Janssen, Speakers bureau: Mitsubishi-Tanabe, Abbott, Eisai, Chugai, Janssen, Santen, Pfizer, Astellas, Daiichi-Sankyo, GSK, AstraZeneca, Otsuka, Actelion, Eli Lilly, Nippon Kayaku, Quintiles Transnational, Ono, UCB Pharma, K. Yamamoto Grant/research support from: Pfizer, Abbott, Santen, Mitsubishi-Tanabe, Eisai, UCB Pharma, Consultant for: Pfizer, Abbott, BMS, Roche, Chugai, Mitsubishi-Tanabe, Eisai, UCB Pharma, T. Takeuchi Grant/research support from: Abbott, Astellas, BMS, Chugai, Daiichi-Sankyo, Eisai, Janssen, Mitsubishi-Tanabe, Nippon Shinyaku, Otsuka, Pfizer, Sanofi-Aventis, Santen, Takeda, Teijin, Consultant for: AstraZeneca, Eli Lilly, Novartis, Mitsubishi-Tanabe, Asahi Kasei, Speakers bureau: Abbott, BMS, Chugai, Eisai, Janssen, Mitsubishi-Tanabe, Pfizer, Takeda, H. Yamanaka Grant/research support from: Abbott, Astellas, BMS, Chugai, Eisai, Janssen, Mitsubishi-Tanabe, Pfizer, Takeda, UCB Pharma, Consultant for: Abbott, Astellas, BMS, Chugai, Eisai, Janssen, Mitsubishi-Tanabe, Pfizer, Takeda, UCB Pharma, N. Ishiguro Grant/research support from: Takeda, Mitsubishi-Tanabe, Astellas, Chugai, Abbott, BMS, Eisai, Janssen, Kaken, Pfizer, Speakers bureau: Takeda, Mitsubishi-Tanabe, Astellas, Chugai, Abbott, BMS, Eisai, Janssen, Kaken, Pfizer, Taisho-Toyama, Otsuka, K. Eguchi Employee of: UCB Pharma, A. Watanabe Grant/research support from: Astellas, Daiichi-Sankyo, Kyorin, Shionogi, Taisho, Dainippon-Sumitomo, Taiho, Toyama Chemical, Meiji Seika, Speakers bureau: Abbott, MSD, Otsuka, GSK, Shionogi, Daiichi-Sankyo, Taisho-Toyama, Dainippon-Sumitomo, Mitsubishi-Tanabe, Toyama Chemical, Bayer, Pfizer, H. Origasa Consultant for: Astellas, UCB Pharma, T. Okamoto Employee of: UCB Pharma, T. Shoji Employee of: UCB Pharma, N. Miyasaka Grant/research support from: Pfizer, Takeda, Mitsubishi-Tanabe, Chugai, Abbott, Eisai, Astellas, T. Koike Speakers bureau: Pfizer, Chugai, Abbott, Mitsubishi-Tanabe, Takeda, Eisai, Santen, Astellas, Taisho-Toyama, BMS, Teijin, Daiichi-Sankyo, UCB Pharma